La vigencia de la ley transitoria de municipalidades de 1857 y su naturaleza declarativa de interés nacional: a propósito del caso del centro poblado de Iquicha - Villalobos Villalobos, Vicente Brayan (Pontificia Universidad Católica del Perú, 2022)
During the provisional government of marshal Ramón Castilla (1855-1858), the National Convention installed in 1855, promulgated the Transitory Law of Municipalities on January 2, 1857. This law provided for the creation of municipalities in 691 districts included in the then existing provinces and departments, among which the district of Iquicha, located in the province of Huanta, region of Ayacucho, is mentioned. However, due to socio-political events and conflicts that affected the cohesion, life and development of this community, the demarcation action was not carried out. Already in 2022, the author of this work was contacted with some representatives of the Iquichana community –resettled in a perfectly determinable high Andean area as they were told– to take some legal action aimed at demanding the Peruvian State implement the respective district.Thus, this text derives from the thesis that the author raised in a compliance process initiated against the Department of Demarcation and Territorial Organization of the Presidency of the Council of Ministers, due to the reluctance of this body to execute the aforementioned law of municipalities (material inactivity of the Public Administration). To achieve this objective, the author claims that the law in question has a declaratory nature of national interest, despite not containing the linguistic statement used by the current legislative technique for the drafting of declarative laws. During the development of his reasoning and argumentation, he addresses several issues closely linked to the controversy, such as the validity and effectiveness of the norms, the methods of legal interpretation, the material content of the declarative laws, the collision between the constitutional precedent “Villanueva Valverde” and the new regulation of the compliance process, among other concepts and legal categories. Likewise, to contextualize the case and highlight the social problems of the Iquichano people, it integrates some sociological and historical studies of this community.

Durante el gobierno provisional del mariscal Ramón Castilla (1855-1858), la Convención Nacional instalada en 1855 promulgó la Ley Transitoria de Municipalidades el 2 de enero de 1857, disponiendo la creación de municipalidades en 691 distritos comprendidos en las provincias y departamentos entonces existentes, entre los cuales se menciona al distrito de Iquicha, ubicado en la provincia de Huanta, región de Ayacucho. Sin embargo, por acontecimientos y conflictos sociopolíticos que afectaron la cohesión, vida y desarrollo de esta comunidad, no se concretó dicha acción demarcatoria. Ya en el 2022, el autor del presente trabajo fue contactado por algunos representantes de la comunidad iquichana –reasentada en una zona altoandina perfectamente determinable según se lo manifestaron– para emprender alguna acción legal destinada a exigir al Estado peruano la implementación del respectivo distrito.Así, este texto deriva de la tesis que el autor planteó en un proceso de cumplimiento incoado contra la Secretaría de Demarcación y Organización Territorial de la Presidencia del Consejo de Ministros, debido a la renuencia de este órgano para ejecutar la referida ley de municipalidades (inactividad material de la Administración Pública). Para lograr este objetivo, el autor sostiene que la ley en cuestión tiene naturaleza declarativa de interés nacional, a pesar de no contener el enunciado lingüístico usado por la técnica legislativa actual para la redacción de las leyes declarativas. Durante el desarrollo de su razonamiento y argumentación, aborda varios temas estrechamente vinculados a la controversia, tales como la validez, vigencia y eficacia de las normas, los métodos de interpretación jurídica, el contenido material de las leyes declarativas, la colisión entre el precedente constitucional “Villanueva Valverde” y la nueva regulación del proceso de cumplimiento, entre otros conceptos y categorías jurídicas. Asimismo, a fin de contextualizar el caso y evidenciar la problemática social del pueblo iquichano, integra algunos estudios sociológicos e históricos de esta comunidad.
The validity of the transitory law of municipalities of 1857 and its declaratory nature of national interest: regarding the Iquicha´s case
Keywords: Territorial demarcation and organization; District of Iquicha; Declaratory laws of national interest; Normative validity and effectiveness; Methods of legal interpretation; Demarcación y organización territorial; Distrito de iquicha; Leyes declarativas de interés nacional; Validez y eficacia normativa; Métodos de interpretación jurídica; https://purl.org/pe-repo/ocde/ford#5.05.01